1991
DOI: 10.1007/bf00169624
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning of the maoA gene and overproduction of a soluble monoamine oxidase from Klebsiella aerogenes

Abstract: We cloned the structural gene for monoamine oxidase (maoA) from Klebsiella aerogenes into a pKI212 vector in an maoA mutant strain of K. aerogenes. Deletion analysis and complementation tests of the recombinant plasmid showed that the maoA gene was located entirely within a 4.1-kb segment. In an maoA mutant strain harbouring the cloned maoA gene, synthesis of monoamine oxidase was induced by addition of tyramine and related compounds. Transfer of a plasmid containing the maoA gene into a monoamine oxidase-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The effect of tyramine on the synthesis of monoamine oxidase in the mutant strain MKN63 (maoA) with or without plasmid pTO58, which contains the monoamine oxidase gene (28) (Fig. 1), was tested.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of tyramine on the synthesis of monoamine oxidase in the mutant strain MKN63 (maoA) with or without plasmid pTO58, which contains the monoamine oxidase gene (28) (Fig. 1), was tested.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial strains used in this study are listed in Table 1. pKI212 (18), a plasmid conferring resistance to kanamycin (Kmr), and pTO58, a plasmid containing the maoA gene from K aerogenes W70, were constructed previously (28). pMC1403 (4), a plasmid containing the lacZ gene without the promoter region, was provided by A. Nakazawa (Yamaguchi University).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the N-terminal region, this is not surprising since a stretch of about 100 amino acids is lacking in the N-terminal region in the amine oxidases of Gram-positive bacteria . Okamura et al (1976) and Sugino et al (1991) reported an amine oxidase in K . aerogenes ( K . pneumoniae) which was a membrane-integrated, hydrophobic enzyme, but they were unable to isolate it.…”
Section: Comparison With Other Copper-quinoprotein Amine Oxidasesmentioning
confidence: 98%